WORKSHOP INTERNET OF THINGS MAHASISWA PROGRAM STUDI MANAJEMEN INFORMATIKA UNIVERSITAS MERDEKA MADIUN - Sukadi (JURNAL DAYA-MAS, 2025)
Internet of Things technology has now become a trend or is widely used to meet the needs of life or lifestyle of the community. To prepare students to face the trend in society, an Internet of Things workshop was held with the theme "Internet of Things for Beginners: Android" for students of the Informatics Management Study Program, Merdeka Madiun University and is also open to the Merdeka Madiun University community. The workshop was carried out using interactive learning and actively involving participants. Workshop participants were immediately given practical work using Internet of Things technology, in this case the DHT11 sensor connected to the internet and also a Smartphone used to monitor temperature and humidity, which can later be applied to smart home technology or smart farming technology. The results of this workshop, students can better understand Internet of Things technology which is currently starting to become a trend in its use in society so that students can be better prepared to enter society after graduating and also have an understanding of the implementation of the DHT11 sensor in smart homes and also smart farming.